Tingkat Efektivitas Pelaksanaan Program Intervensi Sanitasi Total Berbasis Masyarakat (STBM)-Stunting di Desa Bayumundu Kecamatan Kaduhejo Kabupaten Pandeglang - Muh. Akbar Al-Bantani; Ipah Ema Jumiati; Agung Satrio Wicaksono (Universitas Batanghari Jambi, 2022)
This study aims to measure level of effectiveness The Community Lead Total Sanitation (CLTS) – Stunting Intervention Program in reducing the risk of stunting that occurs within the household scope in Bayumundu Village, Kaduhejo District, Pandeglang Regency. An research methodology using quantitative method with a descriptive analysis approach. The sampling method utilized is a probability sampling method with proportional area sampling, which means that method for choosing samples is based on the study's designated area. As result of sampling, 76 respondents made up the research sample. The study’s research shows that the program's activities are not operating effectively, that community development is not being monitored consistently, the community that the program is intended to serve is not easily accessible during data gathering, lack of tranpraency information about the construction costs for latrine santation, and and a lack of motivation to construct their own latrines. The study's results show that a level of effectiveness of CLTS-Stunting Intervention Program was implemented in Bayumundu Village, Kaduhejo District, Pandeglang Regency, which received a percentage value of 70.02 %, placing it in the